2021
DOI: 10.3390/min11121393
|View full text |Cite
|
Sign up to set email alerts
|

A Geological-Geophysical Prospecting Model for Deep-Seated Gold Deposits in the Jiaodong Peninsula, China

Abstract: The North China Craton is one of China’s major gold-producing areas. Breakthroughs have been continually made in deep prospecting at depths of 500–2000 m in the Jiaodong Peninsula, and geophysical methods have played an important role. Given that the geophysical signals of deep-seated gold deposits are difficult to detect, due to their thick overburden layers, conventional geophysical methods are not suitable for deep prospecting. Therefore, this study upgrades the geological-geophysical prospecting model, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
2
0
2
Order By: Relevance
“…Como antecedentes se tiene que el método CSAMT de alcance profundo fue aplicado y contribuyó significativamente en el descubrimiento de los yacimientos epitermales de alta sulfuración Veladero en Argentina (Quantec Geoscience, 2022) y Salares Norte en Chile (Brewer et al, 2017). También en la exploración de otros tipos de yacimientos en Perú como Cerro Lindo (Bueno, 2019), y en otras áreas de China como Jianshui (Guo et al, 2019), Zhongxingtun (Jiang et al, 2020, Jiaoding (Song et al, 2021) y Layikeleke (Yan et al, 2021).…”
Section: Introductionunclassified
“…Como antecedentes se tiene que el método CSAMT de alcance profundo fue aplicado y contribuyó significativamente en el descubrimiento de los yacimientos epitermales de alta sulfuración Veladero en Argentina (Quantec Geoscience, 2022) y Salares Norte en Chile (Brewer et al, 2017). También en la exploración de otros tipos de yacimientos en Perú como Cerro Lindo (Bueno, 2019), y en otras áreas de China como Jianshui (Guo et al, 2019), Zhongxingtun (Jiang et al, 2020, Jiaoding (Song et al, 2021) y Layikeleke (Yan et al, 2021).…”
Section: Introductionunclassified
“…Electromagnetic methods have been extensively employed in the exploration of ore deposits, including rare earth mineral exploration [21], as well as the exploration of coppernickel deposits [22], lead-zinc ore deposits [23], and gold deposits [24]. These research endeavors have effectively demonstrated the potential applications of electromagnetic techniques in mineral exploration.…”
Section: Introductionmentioning
confidence: 99%
“…The margin of the craton is often abnormally rich in gold, molybdenum, and rare earth element (REE) deposits [1][2][3][4]. Several large-scale Au mineralization provinces formed around the NCC destruction zone during the Mesozoic, such as the Jiaodong, Xiaoqinling, Liaodong, and Jidong mineralization provinces [2,[5][6][7][8][9][10][11]. The genesis of these Au deposits has received much attention, especially in the Jiaodong region [5,6,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%